Strategi Pengembangan Wisata Keramba Berbasis Masyarakat di Pantai Nelayan Canggu - Ni Putu Sintia Dewi; Dewa Ketut Suryawan (Journal of Contemporary Public Administration, 2024)
This research is research on strategies for developing community-based cage tourism at Nelayan Beach, Canggu. This research aims to examine the development of the physical and non-physical potential of Canggu Village with the Tri Hita Karana philosophy, which can be managed sustainably by the local community in order to improve welfare. This research is qualitative research with a descriptive approach. The data collection techniques used in this research are interviews, observation, and documentation. The informants in this research were six people, consisting of 2 government officials, two fishermen representatives, and two representatives from youth organizations using a purposive sampling method. The research results show that Canggu Village has a work plan for monitoring adjustments and maintenance so that the Keramba Tourism Development Strategy becomes sustainable. The Work Plan is regulated in MUSDES (Village Conference). Through MUSDES, community participation is optimized. The implementation of tourism development has so far gone well, with the involvement of all aspects of society in accordance with the plans that were carried out.